Calaspargase pegol and pegaspargase cause similar hepatosteatosis in mice - Veronica Ruiz-Torres; Jennifer J. Chia; Michael Cohen; Jia Tan; Teresa Rushing; Jose Tinajero; Etan Orgel; Steven D. Mittelman (Haematologica)
Not available.